2020
DOI: 10.1590/0103-8478cr20190689
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate (Punica granatum L.) peel lyophilized extract delays lipid oxidation in tuscan sausages

Abstract: Pomegranate (Punica granatum L.) contains a high concentration of antioxidant and phenolic compounds. Pomegranate peel extracts at different concentrations were used as natural antioxidant to increased the lipid stability of fresh Tuscan sausages, comparing with sodium erythorbate (SE). Peels were subjected to ultrasound-assisted aqueous extraction and lyophilization. The extract was previously characterized throught phenol and flavonoids determination. The Tuscan Sausages were prepared, and color, pH, peroxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 35 publications
3
14
1
1
Order By: Relevance
“…Thereafter, the semisolid methanolic extract was frozen at −70°C ± 10°C for 24 h inside of an ultra freezer (ColdLab, CL 600-80) for lyophilization (Terroni, model LS3000) for 26 h, and the resulting product was the lyophilized pomegranate peel extract, which was stored at −20°C in a hermetically sealed, light protected container (Zago et al, 2020).…”
Section: Preparation Of Extractmentioning
confidence: 99%
“…Thereafter, the semisolid methanolic extract was frozen at −70°C ± 10°C for 24 h inside of an ultra freezer (ColdLab, CL 600-80) for lyophilization (Terroni, model LS3000) for 26 h, and the resulting product was the lyophilized pomegranate peel extract, which was stored at −20°C in a hermetically sealed, light protected container (Zago et al, 2020).…”
Section: Preparation Of Extractmentioning
confidence: 99%
“…Furthermore, it was reported that the addition of pomegranate peels to chicken burgers improved the oxidative stability by decreasing peroxide and TBARS values [ 133 ]. Various researchers have also indicated that extracts from pomegranate coproducts inhibit primary and secondary lipid oxidation in several meat products, including goat meat patties [ 145 ], cooked beef meat sausages [ 160 ], chicken breast meat [ 130 ], and Tuscan sausages [ 33 ]. According to them, the inhibitory effect is due to blocking radical chain reaction in the oxidation process, attributed to their phenolics content [ 13 , 161 ].…”
Section: Pomegranate In Muscle Food Applicationsmentioning
confidence: 99%
“…Incorporation of PPP did not have any negative effect on the sensory characteristics of beef sausages [ 127 ] and Tuscan sausages [ 33 ]. Likewise, the minced meat of Indian mackerel ( R. kanagurta ) treated with pomegranate peel was acceptable up to the eighth day of storage compared to four days for the control samples [ 139 ].…”
Section: Pomegranate In Muscle Food Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Para obtenção dos extratos etanólicos de própolis preparou-se 20 mL de cada solução nas concentrações de 10, 15 e 20% em álcool etílico 40%. Na sequência as soluções foram submetidas a banho de ultrassom em potência de 40 KHz durante 2 horas a temperatura máxima de 40ºC (Zago et al, 2020). Após, filtrou-se a solução em papel filtro e removeu-se o sobrenadante.…”
Section: Preparo Dos Extratos Etanólicos De Própolis (Eep)unclassified